The importance of environmental education in preventative healthcare - Kowalski, Ryszard; Grott, Edward (Studia Ecologiae et Bioethicae, 2014)
Environmental education frequently referred to as ecological education, is commonly associated with the description and shaping of human relationships with the natural environment. It points to the examples of the anthropocentric transformation of nature and the consequences thereof. The deeper analysis leads to the conclusion that the existing emphasis on environmental education was on natural aspects while neglecting no less important social issues, including human health. !is article is devoted to demonstrating the interrelationships and dependencies of environmental education and preventive healthcare, from definition through to various activities and finally effects. !e article clearly promotes being active, highlighting the importance of being involved in the development of gardens, which are important both in terms of the protection of the natural environment, through the development and diversification of the landscape, and in the maintenance of the good physical and mental condition. In summary, the article puts forward the notion that is going through life, it is worthwhile to really care about one’s health and the natural environment, especially since one is dependent on the other.